Exploration of Major Cognitive Deficits in Medication-Free Patients With Major Depressive Disorder - Liu, Jin; Dong, Qiangli; Lu, Xiaowen; Sun, Jinrong; Zhang, Liang; Wang, Mi; Wan, Ping; Guo, Hua; Zhao, Futao; Ju, Yumeng; Yan, Danfeng; Li, Haolun; et al. (Frontiers in Psychiatry, 2019)
Background: Major depressive disorder (MDD) is associated with a wide range of cognitive deficits. However, it remains unclear whether there will be a major cognitive deficit independently caused by depression at acute episodes of MDD. Methods: A comprehensive neurocognitive test battery was used to assess the executive function, processing speed, attention and memory in 162 MDD patients and 142 healthy controls (HCs). A multivariate analysis of variance, hierarchical regression analyses and general linear regression analyses were used to explore the possible major cognitive deficits and their predictor variables. Results: MDD patients showed extensive impairment in all four cognitive domains. Impairment of executive function and processing speed were found to persist even with other cognitive domains and clinical variables being accounted for. Executive function and processing speed were further predicted by total disease duration and depression severity, respectively. Conclusions: Executive function and processing speed may be two distinct major deficits at acute episodes of MDD. Furthermore, the executive function is likely originated from the cumulative effect of disease duration and processing speed is possibly derived from the temporary effect of current depressive episode.